A Conical-Scanning Microwave Limb Sounder for Atmospheric Measurements - Joe W. Waters; Nathaniel J. Livesey; Michelle L. Santee; Paul C. Stek; Richard E. Cofield; Peter H. Siegel; Jonathan H. Jiang; Qinbin Li; Gloria L. Manney; William G. Read; Duane E. Waliser; Dong L. Wu (IEEE Journal of Microwaves)
We describe a novel scanning microwave limb sounder (SMLS) instrument that performs rapid and broad azimuth conical scans of Earth's limb while simultaneously scanning the limb in the vertical. This azimuthal scanning capability gives dramatic improvement in temporal and spatial coverage over that of previous limb sounding instruments. In a 1500-kilometer altitude, 52°-inclination Earth orbit, SMLS provides 6–8 vertical profile measurements separated by 1.9 hours every 24 hours everywhere between ±65° latitude, and 2–4 such measurements everywhere between ±(65–82°). Horizontal resolution is ∼50×50 km. Vertical resolution is ∼2 km for water vapor and cloud ice and ∼1–3 km for chemical species. In an equatorial orbit, emphasizing the tropics and subtropics, SMLS produces profile measurements every 1.9 hours everywhere between ±35° latitude. SMLS measurements address scientific issues of relevance to the upper troposphere, stratosphere, mesosphere, and lower thermosphere regions of the atmosphere (heights from ∼10 km to ∼100 km).